Identification and characterisation of novel bacteriocins active against Clostridioides difficile - Chapman, Sarah May Olivia (2020)
Clostridioides difficile is a Gram-positive, spore forming, anaerobic bacilli which is a leading causative agent of antibiotic associated diarrhoea and represents a significant burden to medical systems worldwide. The current treatment for C. difficile is antibiotics, including vancomycin, which are also a major risk factor for the disease. Due to this and the growing concern of the increasing prevalence of organisms with antibiotic resistance, including vancomycin resistance, a need for novel treatments has been repeatedly expressed. Bacteriocins are a group of antimicrobials undergoing increasingly extensive research for their applications as antimicrobials in the medical industry. In this study, putative bacteriocin harbouring organisms demonstrating antimicrobial activity towards clinically relevant strains of C. difficile were isolated from cow manure, a suggested reservoir of C. difficile, and characterised. In total six discrete organisms were positive for antimicrobial activity and in silico analysis was used to narrow this down to the three most probable candidates carrying novel bacteriocins. One, Streptococcus 30ANiii, was demonstrated to secrete an antimicrobial compound however this could not be attributed to the in silico candidates. Another organism, Lactococcus lactis 10, carried the well-known nisin bacteriocin which was shown to be the agent responsible for the observed antimicrobial activity. The last organism, Bacillus pumilus 1_16, solely harboured a putative novel bacteriocin which was shown to be of a proteinous nature through demonstrating antimicrobial activity after peptides were precipitated using 40% ammonium sulphate. Although the predicted bacteriocin structural gene, bacP, was not successfully expressed in an E. coli host, the putative bacteriocin locus did result in a preliminary demonstration of antimicrobial activity suggesting that this locus encodes a novel bacteriocin. This study presents a novel putative bacteriocin that could be investigated as a future treatment for C. difficile, providing further evidence of the potential of bacteriocins for medical applications.